An Analysis on National Destinies of Selected Indian Novels: Exploring the Role of Indian Novels in Shaping the National Destiny (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Gurcharan Das’ A Fine Family is the great Indianmiddle class novel built around the birth and maturation of the Indiannation-state. The negatives and positives of British rule, the drama of thevaliant freedom struggle, the trauma of the Partition of India, the highs andlows of the nation-building enterprise of the sixties, and, the battle fordemocracy and the creation of a progressive India by a new generation in theturbulent seventies - are all seen from the hitherto neglected perspective ofcommoners. Gurcharan Das attaches great significance to the middle-class familyas a basic unit of the nation-state. He reiterates the role of Partitionrefugees and middle-class entrepreneurs in nation-building. A student ofphilosophy who combines Vedanta with modern liberalism, he strives to reconcileconflicting ideas of spirituality and worldliness in the mind of the modernIndian citizen. In an interview with this researcher, Das emphasized the needfor citizens to follow the path of dharma or duty or right action at the righttime, to be responsive to societal problems in their immediate neighbourhoods.He lamented the loss of the moral core in national life and opined that therole of the writer is to disturb the conscience of the nation. Nevertheless, heforesees India becoming a great middle-class economy and reposes faith in theIndian entrepreneur and the strong Indian society that has grown despite theweak state. At the same time, he calls for a strong state that would swiftlycurb corruption and encourage institutional reforms (Das, Telephone interview).